First report of Diaporthe humulicola causing stem blight in hop plants in Massachusetts - Williams, Noah; Stamborski, Nolan; Back, Chang-Gi; Jung, Geunhwa (Plant disease, 2025)
Humulus lupulus L., the common hop plant, is a commercially cultivated crop used as a beer flavoring agent that has been grown in Massachusetts since the 1600s (Machado et al., 2019 ; Rumney, 1998). In 2018, Diaporthe leaf spot, caused by the fungal pathogen Diaporthe humulicola, was found at hopyard research plots in Connecticut, followed by reports in multiple New York counties in 2023 (Allan-Perkins et al., 2020; Sharma et al., 2023). Additionally, Diaporthe halo blight, caused by the same fungal pathogen, was reported in Prince Edward Island (PE), Canada (Foster et al., 2024). In August of 2021, severe stem blight symptoms with visible fungal fruiting bodies were observed on >50% of plants at a hopyard in Franklin County, MA. Brown spots were observed on stems. Severe infection presented as widespread dark browning on stems, leaves, and cones. Samples were collected from the hop cultivars Mt Rainier (N=5), Magnum (N=1), and Teamaker (N=6). Under brightfield microscopy (400x) conidia congruent with Diaporthe spp. were observed on stem samples. Diseased stems from all cultivars were peeled and cut into 2 to 4 mm2 pieces, then surface sterilized in 70% ethanol for 60s, and 1% NaOCl for 60s. Samples were rinsed in sterile water, dried for 3 min and placed on potato dextrose agar (PDA). Plates were incubated at 25℃ for 5 days. 11 isolates were obtained from stem tissues of 11 plants. Isolates were cultured on PDA. 10 isolates had morphological traits consistent with the pycnidium of holotype UAMH 12076 (Allans-Perkins et al, 2020). Isolate sequences were identical, using one reinfection tests were performed on detached stem segments obtained from field grown mature plants (≥ 1 year) of cvs. Cascade and Magnum.3 wounding methods and an untreated control were used for pathogenicity testing to simulate field conditions. Each treatment had 6 replicates per cultivar and all treatments had an agar plug of inoculum applied to them, then were incubated at room temperature. Wounding with a knife involved peeling off the outer tissue layer, insect damage was simulated by using a needle to puncture the stem 3 times, and friction damage from hop support ropes was mimicked by rubbing rope against the stem. Plugs were removed 5 days post-application. Pathogenicity was observed as fungal growth and necrosis of plant tissue on all non-control methods in all samples 5 days post plug removal, fulfilling Koch's postulates. The pathogenic organism was reisolated from all inoculated tissues, except the control and identified using morphological characteristics and ITS sequence analysis. DNA amplification of the ITS region was performed according to the methods of White et al. (1990). A maximum likelihood phylogenetic tree based on the region was constructed using the MEGA10 program (Saitou & Nei, 1987). Sequence data was collected from NCBI BlastN, then aligned and trimmed. The ITS sequences (NCBI Acc. Nos. PQ555192, PQ555193, PQ555194) from the 3 isolates (UMASS001, UMASS002, UMASS003) matched 100% (543/543bp) with those of the type specimen of D. humulicola, which causes Diaporthe leaf spot and halo blight, collected in CT (NCBI Acc. No. MN152929) and 2 ex-type sequences from CT and Canada respectively (NCBI Acc. Nos. MN152927, NR172855).This is the first report of D. humulicola associated with stem blight disease. Our findings indicate that the same pathogen that infects stems can also infect cones and leaves. Therefore, Diaporthe disease management strategies should target all plant parts.